Utilization Of Multihop Communication Technology Based on Lora for Maintenance of Airport Street Lighting - Eriansyah Sahputra Hasibuan; Albert Panjaitan; Rossi Peter Simanjuntak (International Journal of Health Engineering and Technology, 2025)
This study aims to design and implement a monitoring and maintenance system for airport street lighting using LoRa-based multihop communication technology. This technology was chosen for its ability to transmit data over long distances with low power consumption and to support large wireless sensor networks through multihop mechanisms. The system design consists of hardware components including an Arduino Uno microcontroller, SX1278 LoRa modules, ACS758 current sensors, and BH1750 light sensors; as well as software for real-time lamp condition monitoring. Tests were conducted on Bluetooth HC-05 connectivity, sensor accuracy, LoRa signal strength at various distances, and data transmission time between nodes. The results showed that all components functioned properly, with an average inter-node data transmission time of 540 ms and RSSI values that decreased proportionally with distance but remained stable up to 250 meters. This system has proven effective in improving maintenance efficiency, enabling early fault detection, and supporting more reliable and energy-efficient management of airport street lighting.